1947
DOI: 10.1113/jphysiol.1947.sp004211
|View full text |Cite
|
Sign up to set email alerts
|

The survival of transplanted embryo bone grafted to chorioallantoic membrane, and subsequent osteogenesis

Abstract: The extent to which bone transplants survive and the source of any new bone subsequently formed are still matters of controversy. Three main hypotheses have been put forward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
2

Year Published

1960
1960
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 5 publications
2
21
0
2
Order By: Relevance
“…Moreover, these cells also co-stained with GFP, confirming their avian origin. Similar cell condensations were shown by Hancox, who implanted chick embryo calvaria fragments on CAM for 10 days37. In accordance with our findings, cell condensations (named by Hancox ‘ectodermal pearls’) were located in proximity to the bone tissue37.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, these cells also co-stained with GFP, confirming their avian origin. Similar cell condensations were shown by Hancox, who implanted chick embryo calvaria fragments on CAM for 10 days37. In accordance with our findings, cell condensations (named by Hancox ‘ectodermal pearls’) were located in proximity to the bone tissue37.…”
Section: Discussionsupporting
confidence: 92%
“…Similar cell condensations were shown by Hancox, who implanted chick embryo calvaria fragments on CAM for 10 days37. In accordance with our findings, cell condensations (named by Hancox ‘ectodermal pearls’) were located in proximity to the bone tissue37. These findings are not surprising given the clinical gold standard biomaterial is bone autograft38, which provides a unique osteogenic microenvironment as a consequence of the plethora of growth factors within the bone matrix ( i.e.…”
Section: Discussionsupporting
confidence: 91%
“…The assumption of recirculation in bone grafts is as a rule based on indirect observations of the vasculature during the first week after the transplantation. Some authors report a strikingly early appearance of blood vessels (Hancox 1947, Ray 1972, others a remarkable acceleration of the injectiability of graft vessels from one day to another (Graf 1959, Deleu & Trueta 1965, Forgon & Bornemisza 1970.…”
mentioning
confidence: 99%
“…We formerly described the formation of these cell condensations in association with collagen type II deposition from the CAM, again coexpressing with SOX9 and GFP next to the human bone tissue (Moreno‐Jiménez et al, ). Early studies from Hancox, showed formation of similar cell condensations following engraftment of chick embryo calvaria fragments on CAM. Other authors have implanted agarose or gelatin beads carrying BMP7 and shown the formation of comparable clusters of cells as well as significant stratification of the CAM extracellular matrix (Ramoshebi & Ripamonti, ).…”
Section: Discussionmentioning
confidence: 99%